NEOBANKS: THE ESSENCE AND PROSPECTS OF DEVELOPMENT IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The modern world is very dynamic, changeable and unpredictable. According to recent events in the world, all spheres of life are undergoing changes, including the financial system of countries in which the main role is played by banks. Over the last few decades, the banking system has undergone dramatic changes. The development of the banking services market is impossible without the introduction of innovative technologies and products to improve customer service. Banking institutions that do not have automated software services will not be able to compete with technically equipped banks. That is why in the modern world there is a need for new, innovative types of banking institutions ‒ neobanks.The article examines the peculiarities of the formation and functioning of neobanks in Ukraine and the world, as well as identifies the prospects for their further development. The paper presents theoretical approaches to defining the essence of neobanks and the proposed author’s definition, according to which neobank is an innovative bank that is available to customers through a mobile application, has no classic banking dapartment and interact with customer through Internet platforms.Peculiarities of activity and tendencies of development of the largest European neobanks are generalized. An analysis of the impact of current trends in the banking sector on the reduction of structural units of traditional banks, the readiness of the population for a new type of banking services – services in non-banks. The dynamic of the client base of the largest traditional banks and the most popular neobank in Ukraine ‒ Monobank has been studied. According to a study by Monobank, over the past six years it has grown its customer base more than 6 times, which is significantly higher than that of the largest traditional banks.The article mentions an important condition for the development of non-banks in Ukraine – the improvement of the regulatory framework that would determine the legal status of such institutions, as well as the conditions for licensing and regulation of their activities.In general, the study made it possible to identify the advantages and disadvantages of neobanks, as well as prospects for their development in Ukraine.
Keywords: banking system, neobanks, virtual bank, innovations, monobank, development